2014
DOI: 10.1371/journal.pone.0088707
|View full text |Cite
|
Sign up to set email alerts
|

Fat Oxidation, Hormonal and Plasma Metabolite Kinetics during a Submaximal Incremental Test in Lean and Obese Adults

Abstract: This study aimed to compare fat oxidation, hormonal and plasma metabolite kinetics during exercise in lean (L) and obese (O) men. Sixteen L and 16 O men [Body Mass Index (BMI): 22.9±0.3 and 39.0±1.4 kg.m−2] performed a submaximal incremental test (Incr) on a cycle-ergometer. Fat oxidation rates (FORs) were determined using indirect calorimetry. A sinusoidal model, including 3 independent variables (dilatation, symmetry, translation), was used to describe fat oxidation kinetics and determine the intensity (Fatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 41 publications
3
78
2
3
Order By: Relevance
“…After the intervention, FORs during exercise were higher and whole‐body fat oxidation kinetics were characterized by a greater dilatation and right‐shift translation in both groups. We recently showed that men with obesity and severe obesity presented a lower Fat max and reliance on fat oxidation compared to their lean counterparts . These findings demonstrated that only 2 weeks of training may increase Fat max and FORs, which suggests that fat oxidation may rapidly improve in this population.…”
Section: Discussionmentioning
confidence: 91%
“…After the intervention, FORs during exercise were higher and whole‐body fat oxidation kinetics were characterized by a greater dilatation and right‐shift translation in both groups. We recently showed that men with obesity and severe obesity presented a lower Fat max and reliance on fat oxidation compared to their lean counterparts . These findings demonstrated that only 2 weeks of training may increase Fat max and FORs, which suggests that fat oxidation may rapidly improve in this population.…”
Section: Discussionmentioning
confidence: 91%
“…rc: restricción calórica; eF: entrenamiento físico; kg: kilogramos. máxima oxidación de grasas (MOG) en sujetos sanos no entrenados se encuentra entre 60 y 65% del VO 2máx 39 , pero en pacientes con sobrepeso/obesidad este valor tiende a estar reducido a 45-50% 40 . También se ha observado que la MOG ocurre a una misma intensidad cuando se compara entre cinta rodante y cicloergómetro, pero la tasa de oxidación de grasas (e.g., gramos × minuto -1 ) es mayor en cinta rodante 41 .…”
Section: Ejercicio Continuounclassified
“…esquema resumen de factores relacionados con la intensidad del ejercicio, la utilización de sustratos por el musculo esquelético y la percepción subjetiva del esfuerzo en sujetos obesos y entrenados (datos no publicados de nuestro laboratorio, de Achten y Jeukendrup 42 , Jeukendrup y Achten 75 y lanzi y col. 40,76 ). MoG: intensidad a la cual ocurre la máxima oxidación de grasas;…”
Section: Ejercicio Intermitente De Alta Intensidadunclassified
“…Based on previous experience [22], peak O 2 uptake (V • O 2peak ) and peak power output (PPO) were measured using a maximal ramp incremental test performed to exhaustion on a cycle ergometer (Ebike Basic BPlus, Niskayuna, NY, USA). After a 3-min rest period, the L group began with a 5-min warmup at 60 W (40 W for the O group), followed by a linear increase in PPO (by 30 W;…”
Section: Maximal Exercise Protocolmentioning
confidence: 99%
“…Thereafter, subjects performed a submaximal incremental test. After a standardized 10-min warmup at 20% PPO, the PO was increased by 7.5% PPO every 6 min (until 57.5% PPO or until the respiratory exchange ratio reached 1.0) as previously described [22].…”
Section: Submaximal Exercise Protocolmentioning
confidence: 99%